Translation for The Readers: an Analysis on The Translation of Sean Coveys The 7Th Habits of Highly Effective TeenS - Prabandari, Carla Sih (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2012)
A good translation should be parallel with the source text both in form andin meaning. Yet, because of the uniqueness of each language, parallel in form is oftendifficult to achieve. This paper attempts to analyze the translation of Sean CoveysThe 7th Habits of Highly Effective Teens in terms of a sociolinguistic point of view anddifferent types of equivalence. The analysis and discussion are based on some casesthat I found. Based on the examples, two conclusions can be drawn. First, from thesociolinguistic point of view, the use of SAYA instead of AKU to refer to the authorcreates more distance with the readers. Second, the translator seems to have workedhard to produce a dynamic equivalence of the source text, but in some cases theidiomatic expressions are not well translated. Thus, the results of the translation donot sound as idiomatic as the source text.